FEATURES OF ACCOUNTING AND INDIRECT COSTS SHARING IN PRODUCTION IN THE PHARMACEUTICAL INDUSTRY - N. Ershova (Publishing House of the State University of Management, 2016)
The article describes particular qualities into the method of cost accounting of production in the pharmaceutical industry, sub-sector production of antibiotics and fluids in liquid form. Due to the fact that the range of calculation of cost items for management purposes is determined by the organizations in the pharmaceutical industry by themselves, often a formal approach increases the likelihood of errors in the cost accounting. The authors propose a list of articles and the structure of indirect costs, taking into account their economic content, place of origin, etc., which will reduce the cost of production and make it more accessible to the end customer